2014
DOI: 10.1093/ehjci/jeu054
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of 18F-FDG-PET/CT in the extra cardiac work-up of patients with infective endocarditis

Abstract: 18F-FDG-PET/CT detected lesions of clinical importance in one of seven IE patients and may be a substantial imaging technique for tracing peripheral infectious embolism due to IE. Thus, 18F-FDG-PET/CT may help to guide adequate therapy and thereby improve the prognosis of patients with IE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…There is increasing evidence that FDG positron emission tomography (PET)/computed tomography (CT) may be useful in the management of infective endocarditis, both for detection of septic emboli [9][10][11][12][13] and for diagnosis of prosthetic valve infection. [14][15][16] A study showed that the sensitivity of the modified Duke criteria performed at admission was markedly increased when the presence of an abnormal FDG uptake was added as a major criterion.…”
Section: See Editorial By Sambuceti Et Al See Clinical Perspectivementioning
confidence: 99%
“…There is increasing evidence that FDG positron emission tomography (PET)/computed tomography (CT) may be useful in the management of infective endocarditis, both for detection of septic emboli [9][10][11][12][13] and for diagnosis of prosthetic valve infection. [14][15][16] A study showed that the sensitivity of the modified Duke criteria performed at admission was markedly increased when the presence of an abnormal FDG uptake was added as a major criterion.…”
Section: See Editorial By Sambuceti Et Al See Clinical Perspectivementioning
confidence: 99%
“…Radiolabeled leukocyte SPECT/CT imaging seems to be more specific for the detection of infective endocarditis and infectious foci than 18 F-FDG PET/CT. However, 18 F-FDG PET/CT is likely the preferred imaging technique, because SPECT/CT is less sensitive, more time consuming, and requires leukocyte labeling.…”
Section: Article See P 1113mentioning
confidence: 98%
“…In patients with a high index of suspicion, a normal/inconclusive echocardiographic examination does not therefore rule out DIE, generating a significant rate of inconclusive diagnoses. For improving the accuracy of the Duke criteria, other imaging modalities such as multidetector computed tomography (CT), 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET), and single-photon emission computed tomography (SPECT) have recently gained importance. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] With the use of retrospective ECG-gated acquisitions and intravenous contrast to enhance vascular structures, currentgeneration CT scanners provide enough spatial detail to visualize the valvular structures at several different phases of the cardiac cycle without motion artifact.…”
Section: Article See P 1113mentioning
confidence: 99%
See 2 more Smart Citations